Self–help group untuk menurunkan stres mahasiswa tingkat akhir - Tutut Ananda Widya Putri (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Stress is an individual's perception of stressors and how individuals respond to stressors as indicated by their physical, cognitive, emotional, and behavioral reactions. The subjects in this study were final year students who were working on a thesis. They are demanded by their families to graduate immediately which makes them stressed. The assessment methods used are interview, observation and Perceived Stress Scale (PSS). The intervention used was a self-help group consisting of six sessions and carried out in groups. The target of the intervention is to reduce the stress level of the subject. The results of the intervention showed that the stress level of the subject before the intervention was in the high category decrease in the medium-low category. This shows that the support among group members obtained from self-help groups can help the subjects find appropriate coping strategies to deal with their stress.